Health Care Workers' Perceptions on Factors Affecting Diabetes Self-Management Among Type 2 Diabetes Mellitus Patients in Fiji: A Qualitative Study - Kumar, Lalesh; Mohammadnezhad, Masoud (Frontiers in Public Health, 2022)
Background: Type 2 Diabetes Mellitus (T2DM) is known as the main leading cause of mortality globally. Health Care Workers (HCWs) can assist patients to become aware of self-care and to solve the challenges diabetes presents. This study aimed to explore HCWs perceptions on factors affecting diabetes self-management among T2DM patients of Fiji. Methods: A qualitative study was employed to obtain qualitative data using 2 Focus Group Discussions (FGDs) amongst HCWs who were providing services to T2DM patients attending different clinics in Labasa, Fiji in 2021. The study settings were the Diabetic Hub Centre and the Nasea health Centre Labasa. Purposive sampling was employed to recruit HCWs. The data was collected using semi-structured open ended questionnaires that were audio recorded. The recorded data was transcribed verbatim which was analysed using thematic analysis process. Results: The study comprised of 9 HCWs with majority of females (89%) and age range of 25 to 49 years. Three major themes and seven sub themes were identified. These included Theme 1- “availability of services” with the sub themes of clinical services for T2DM and other support services available for T2DM patients. Theme 2 - “barriers and challenges to diabetes self-management” with the sub themes of health system factors, socioeconomic factors and health system factors. Theme 3- “proposed strategies” with the sub themes included resource and skilled personnels. Conclusion: The findings of this study demonstrate health system challenges such as lack of material resources and human resources that compounded the factors affecting diabetes self-management. HCWs training as diabetes educators, developing policy on diabetes self-management, and introduction of telemedicine to reach patients in remote areas are highly recommended to promote.